2017
DOI: 10.1242/jeb.156919
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses to short-term thermal stress in mayfly (Neocloeon triangulifer) larvae in relation to upper thermal limits

Abstract: Understanding species' thermal limits and their physiological determinants is critical in light of climate change and other human activities that warm freshwater ecosystems. Here, we ask whether oxygen limitation determines the chronic upper thermal limits in larvae of the mayfly Neocloeon triangulifer, an emerging model for ecological and physiological studies. Our experiments are based on a robust understanding of the upper acute (∼40°C) and chronic thermal limits of this species (>28°C, ≤30°C) derived from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 62 publications
5
29
0
Order By: Relevance
“…For example, we did not manipulate O 2 levels and did not include important ancillary data regarding metabolomics, the expression of genes related to oxygen stress, and other physiological parameters. However, we can report that measurements of metabolism in our study and recent results of aerobic-scope studies for other mayflies (Kim et al 2017) suggest that mayfly larvae seem to have sufficient capacity to extract O 2 at CT max . A recent test of the OCLTT (Verberk et al 2016) showed that thermal responses exacerbated the sensitivity of test organisms to hypoxia in the field and the laboratory and often at O 2 levels well above those considered stressful.…”
Section: Volume 37supporting
confidence: 39%
See 2 more Smart Citations
“…For example, we did not manipulate O 2 levels and did not include important ancillary data regarding metabolomics, the expression of genes related to oxygen stress, and other physiological parameters. However, we can report that measurements of metabolism in our study and recent results of aerobic-scope studies for other mayflies (Kim et al 2017) suggest that mayfly larvae seem to have sufficient capacity to extract O 2 at CT max . A recent test of the OCLTT (Verberk et al 2016) showed that thermal responses exacerbated the sensitivity of test organisms to hypoxia in the field and the laboratory and often at O 2 levels well above those considered stressful.…”
Section: Volume 37supporting
confidence: 39%
“…4). This pattern also was observed in the mayfly Neocloeon triangulifer, where aerobic scope was similar at tolerated and chronically lethal temperatures (Kim et al 2017). This result suggests that larvae still have substantial aerobic capacity at a temperature that results in 0 reproductive output.…”
Section: Volume 37mentioning
confidence: 59%
See 1 more Smart Citation
“…Finally, for the present study, the acute and chronic toxicity tests were conducted at 25 °C like some previously published studies (Soucek and Dickinson 2015; Struewing et al 2015; Weaver et al 2015; Raby et al 2018; Soucek et al 2018). The clone in our culture (WCC‐2; Stroud Water Research Center) was originally collected in White Clay Creek, Pennsylvania, USA, which reaches a maximum temperature of approximately 23 °C (Kim et al 2017). The Illinois Natural History Survey (2019) insect collection database reports collections of Centroptilum (the former generic name for Neocloeon ) throughout southern Illinois, including the Kaskaskia River, which has an average temperature >25 °C over the summer months (US Geological Survey 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we ask the question whether pathways related to energy or anaerobic metabolism are affected at ecologically relevant thermal limit. We design the experiment to ramp mayfly Neocloeon triangulifer (Ephemeroptera: Baetidae) larvae at a rate of 1°C/hour from 22°C (a temperature associated with excellent survival and reproductive output) to 30 °C (a temperature that is chronically lethal to larvae based on life history survivorship data (Kim et al, accepted). We use both NMR and GC-TOF-MS techniques to observe and compare metabolite changes from samples taken at 22 °C and 30 °C…”
Section: Introductionmentioning
confidence: 99%